Exaerete salsai sp. n. (Hymenoptera: Apidae): a new orchid bee from eastern Brazil - Nemésio, André (Zootaxa, 2011)
Exaerete salsai sp. n. (Hymenoptera: Apidae: Apini: Euglossina) is described from southern Bahia and northeastern Minas Gerais, eastern Brazil. Its relationships with the other members of the genus are discussed, and it is considered to be a close ally of the Amazonian Exaerete trochanterica (Friese, 1900) and the Central American Exaerete kimseyae Oliveira, 2011.